Powering Up User Loyalty: Exploring Multidimensional Platform Value and Service Quality in the PLN Mobile Electricity Service Application Platform - Pradipta, Fristyan; Aruan, Daniel Tumpal H (Syntax Literate, 2024)
The objective of this research is to explore how digital interactive platforms can assist companies in cultivating brand loyalty for their platforms. This study employs a quantitative approach, collecting a total of 310 questionnaires from PLN Mobile users, a platform operated by the largest electricity company in Indonesia. Respondents were selected using non-probability random sampling, and Structural Equation Modeling was employed as the analysis tool. The findings reveal that among the three multidimensional platform values (functional, cost, and contextual) only functional platform value lacks significant influence on perceived value. Additionally, within the context of PLN Mobile application users, service quality demonstrates a positive and significant direct influence on perceived value, platform brand image, and platform brand loyalty. Furthermore, perceived value exhibits a significant direct influence on continuance intention and platform brand image, although it does not significantly influence platform brand loyalty directly in this context. This research offers a new theoretical framework and managerial insights for value creation in digital interactive platforms. It contributes to the body of knowledge by demonstrating the relationships between various factors influencing brand loyalty in the context of digital platforms. The implications of the research findings on management and business practices are significant. Companies can utilize the insights provided by this research to enhance their digital platform offerings, improve customer satisfaction, and ultimately foster brand loyalty. Additionally, policymakers can use these findings to shape regulations and policies that promote innovation and competitiveness in the digital platform in service industry.